State regulation of development of investment programs in the sphere of construction in the conditions of cyclicality of the economy - Skripnik, А. L.; Ivanchenko, A. M. (Ways to Improve Construction Efficiency, 2019)
The article is devoted to determining the effect of cyclicality on the development of the Ukrainian economy and the implementation of state investment programs in construction. The purpose of the article is to substantiate the feasibility of state anti-cyclical regulation of construction through the implementation of state investment programs and to develop proposals for the structure and order of formation of the appropriate organizational and economic mechanism. To do this, the impact of cyclicality on the development indicators of the construction industry should be determined, and the nature of the relationship between Ukraine's GDP of construction and investment activity and the list of public investment programs related to construction should be considered. The main indicators chosen to determine the economic cycles are GDP, GDP of construction. The state investment programs, which are directly or indirectly related to construction, are reviewed, ways and methods of their state regulation are determined. State support for the implementation of investment projects is provided by: co-financing at the expense of the state budget, providing state guarantees in accordance with the law on credit funds for the implementation of investment projects, crediting at the expense of the state budget funds, offsetting from the state budget interest on loans necessary for the implementation of investment projects . The analysis of sources of financing of capital investments in Ukraine for the years 2002-2018 was carried out, we determined that the share of state and local budgets in the sources of financing was the largest in 2014 (15%), 2010, 2017 and 2018 (more than 10% ). Moreover, the share of public investments is gradually decreasing, while the financing of investment projects at the expense of local budgets increases annually. It is determined that increasing the financing of state investment programs at the bottom of the economic cycle can stimulate the growth of the economy in the next phase. State regulation of investment programs in the construction sector is an effective tool for counter-cyclical economic management.